EMPOWERING ORPHANAGE CHILDREN WITH INTEGRITY THROUGH GREEN ENGLISH PROGRAM - Thahara, Yopi; Lailiyah, Sufil; Fitriyah, Nina Sa’idah; Novitasari, Nine Febrie; Firdaus, Ahmad Yusuf (Annual International Conferences on Language, Literature, and Media, 2023)
This article presents the results of the community service program with partner Tunas Melati Orphanage, Pokaan, Situbondo. From the initial observation, it was found that many of the partner's foster children had low self-esteem. In fact, as the nation's future, they must grow and develop into humans with integrity to compete globally. They need social sensitivity, fundamental skills, and good English language skills to be part of the global community. Based on the discussion with the program partner, it was found out that the priority problems faced are (a) Tunas Melati Orphanage’s foster children have inferior feelings towards themselves and (b) English language skills possessed by Tunas Melati Orphanage foster children are still lacking to be used in socializing. Based on the description of priority problems and solutions to the existing problems, the method implemented was strengthening the integrity character, which was inserted in English learning, and was implemented into several activities. The activity results show that the Tunas Melati Orphanage foster children have shown indicators of social sensitivity and social skills even though they have yet to be maximized, likewise, in English language skills which only reached Level 1. This is because this activity has only been partially carried out. Therefore, further activities need to be carried out immediately to see the overall results.